Addition of alfa fetoprotein to traditional criteria for hepatocellular carcinoma improves selection accuracy in liver transplantation. (3rd August 2018) - Sternby Eilard, Malin; Holmberg, Erik; Naredi, Peter; Söderdahl, Gunnar; Rizell, Magnus
Abstract: Objectives: Liver transplantation in hepatocellular cancer (HCC) is curative only for a selection of patients. Commonly used criteria are mostly based on tumor size and number. However, patients within criteria do have tumor recurrences after transplantation and patients outside criteria are excluded even though some could benefit from transplantation. The tumor marker alpha fetoprotein (AFP) is associated with poor outcome and has already been reported to improve selection. We investigated the hypothesis that AFP level combined with traditional selection criteria could ameliorate the selection accuracy for liver transplantation in HCC. Materials and methods: A retrospective national cohort study in 336 patients who had liver transplantation for HCC in Sweden 1996–2014. Results: AFP cut-off levels of 20, 100, 1000 and >1000 ng/mL stratified both survival and tumor recurrence, with estimated 5-year survival rates of 74, 61, 49 and 31%, respectively. A simple score, combining three risk levels according to Milan and UCSF fulfillment with three levels of AFP, increased predictive accuracy. A high score identified 35 at-risk patients with estimated post-transplant 5-year survival rate of only 29% compared to 50% for 76 patients excluded by UCSF. More patients were within the combined score cut-off compared to within UCSF, but 5-year survival was similar, 67% versus 66%. Conclusion: AFP combined with traditional selection criteria ameliorates the selection accuracy for liver transplantation in HCC.